Chávez, Alex E. 2017. Sounds of Crossing: Music, Migration, and the Aural Poetics of Huapango Arribeño. Durham, NC: Duke University Press - Banerjee-Datta, Nandini Rupa (Current Musicology, 2018)
Alex Chávez’s bold and engaging study of huapango arribeño in the everyday lives of Mexican migrants fills a void in anthropological and ethnomusicological scholarship. Based on his 2010 dissertation at the University of Texas at Austin, Sounds of Crossing is an anthropologically based study of how lived politics informs performance in the poetic genre of huapango arribeño, an understudied musical form that originated in the Mexican states of Guanajuato, Querétaro, and San Luis Potosí. Chávez argues that huapango arribeño is crucial in meeting everyday needs for intimacy, place, and belonging—“beyond culture, beyond illegality, and irrespective of geography; through it postnational subjectivities are fashioned and necessary, aquí (here), not allá (out there)” (54). His book includes colorful photographs from the everyday lives of performers and poignant transcriptions of conversations and songs, as well as musical notation—all of which add to his ethnography’s depth and multiplicity, reaffirming his argument that his book is not so much the study of huapango arribeño as an object but as “an analytical lens into the contemporary experiences of Mexican migrants” (34). Sounds of Crossing is teeming with moments of intimacy, and a genuine attention to humanity—a trait that is seldom associated with the lives of Mexican migrants in the United States. The book articulates a theoretical network of affect, semiotics, voice, and place through the scholarship of Américo Paredes, Michel de Certeau, Gilles Deleuze and Félix Guattari, Kathleen Stewart, and José Limón to name a few. Chávez positions himself among these scholars with the assertion that the material enactment of voicing takes place. Voicing, he says, “constructs mattering maps that represent the ways social actors move through the world, or desire to do so” (8). Sounds of Crossing crosses back and forth over the border, from Xichú to Austin, from San Luis Potosí to Tennessee, and takes shape around the individuals who sing, perform, and enjoy huapango arribeño—the stories of their lives, the politics that have inspired their lyrics, the clever and metalinguistic ways in which huapangueros, or the troubadours, build discourse throughout the course of a night, the interactions between huapangueros and the audience, and the ways in which huapangueros create an aural space with a sense of purpose and dignity. Chávez transcribes the back and forth compositions of particular performances with precision to show the unfolding debate of the night. He writes, “This coconstituted reflexivity focused on each other’s [the troubadours’] linguistic, poetic, and performative competences involves an assessment of how sound and well-informed instances of poetic discourse actually are, that is, how grounded they are in grammatical and performative patterns” (125). Chávez sets the tone of the book through descriptions of Doña Rosa’s home—a space full of life and overflowing with arduous tales of migration and love. Her home creates a point of reference throughout the book. It is a meeting place for huapangueros and a space for collective remembering. In Chapter 1, we read about the aural formation of Mexican culture through the construction of a nationalized space in Mexico and a racialized one in the United States. Chávez elaborates on the symbolism of the Mexican rancho—a small rural piece of land, but also “a repository for an assumed collective heritage rooted in expressive cultural practices tied to subsistence ranching and horsemanship” (44)—and introduces the ranchero chrono-trope as an imagining of the rancho as a proto-national space-time that represents authentic Mexican culture, or a “spaciotemporal construct” (46). Drawing from Mikhail Bakhtin’s concept of the chronotope, or the intrinsic connectedness in literature of spatial and temporal relationships, Chávez uses the concept of the ranchero chrono-trope as a way of understanding the history behind essentialist and racialized representations of Mexican culture. Chávez builds his narrative in this chapter by lucidly connecting the imperialist Mexican-American War with present-day oppressive politics in the United States. He writes, “It was a war of modernity waged against a supposedly barbarous people and justified as an integral part of God’s will to make the geographic expanse of America fruitful and free” (49). Chávez historically maps the construction of the Mexican other and connects it to his musical analysis of huapango by challenging conventional narratives that position huapango as a static tradition. By highlighting the multiplicitous origins of huapango, we no longer see the genre as an “othered” object, but as an organic and dynamic product of historical, political, and cultural events. Listening to stories of individuals and interacting with huapango, rather than providing an account of it, is Chávez’s way of understanding the US-Mexico border. In his detailing of the poetic and semiotic structures of huapango arribeño in Chapter 2, we learn about the different musicians and their roles, and about types of compositional structures such as the poesía, decimal, and jarabe. Through transcriptions of compositions between huapangueros Pablo and Celso, notations, and thick description, we are plunged into the multisensorial and metalinguistic world of a topada, or a performance, in Chapter 3 and are led to the Festival del Huapango Arribeño y de la Cultura de la Sierra Gorda in Xichú, Mexico. We attend different topadas throughout the book, in both Mexico and the United States, and through Chávez’s visceral descriptions of both the constructed outdoor venues and adapted venues inside school gymnasiums, it is as if we can hear the stomping of dancers and feel the heat rising from their bodies. The dense and intimate ethnographic fieldwork once again reiterates Chávez’s insistence on viewing the humanity of Mexican migrants. In Chapter 4, Chávez constructs his theoretical discourse on place through accounts of racialized ethnonationalism. He sees place as porous and shimmering, a meeting of meaning, economic relations, and shared experiences, both physical and metaphysical. Chapter 5 continues his theoretical discussion of place, bringing in the body as the primary somatic medium of being in place. He emphasizes the construction of connection and dignity by linguistically analyzing the saludado, the improvised greeting and a moment of ordinary interpersonal talk, by the troubadour. Anyone in the audience can request a saludado for a loved one, in turn giving form to the troubadour’s compositional effort. The improvised moment compresses time and space momentarily and reignites the space with intimacy. Saludados, Chávez writes, “may be understood as embodied acts of self-valorization expressed by people who are subject to genocidal policies designed to kill them as they cross the border and to exploit them once they make it across” (271). They create a moment in space and time that cannot be contained by the border. “It is a necessary aural poetic affirmation of social structure” (276), one that poetically narrows the distance that is felt with the body. Sounds of Crossing is courageous and timely. Chávez writes from a critical anthropological perspective about a subject that is uncomfortable for many: the alienation of undocumented life and the grim reality of oppressive and racist political structures in the United States. As a son of Mexican migrants himself, Chávez paves the way for anthropologists who write about their own communities and engages in the larger project of decolonizing anthropology. As Chávez eloquently puts it, “These circulating forms of often disparaging, damaging, and, more specifically, prejudiced forms of knowledge retain a deep legacy that extends well beyond the academy, which we labor to disarticulate through our scholarship” (319). Sounds of Crossing will be of interest not only to scholars across disciplines and musical genres, as it relates aurality and aesthetics to political and social life, but also to non-academic lovers of music. This is a book of humanity, and a book of stories.